Quantifying infection risks in incompatible living donor kidney transplant recipients. Issue 4 (25th October 2020) - Avery, Robin K.; Motter, Jennifer D.; Jackson, Kyle R.; Montgomery, Robert A.; Massie, Allan B.; Kraus, Edward S.; Marr, Kieren A.; Lonze, Bonnie E.; Alachkar, Nada; Holechek, Mary J.; Ostrander, Darin; Desai, Niraj; et al.
Abstract : Desensitization has enabled incompatible living donor kidney transplantation (ILDKT) across HLA/ABO barriers, but added immunomodulation might put patients at increased risk of infections. We studied 475 recipients from our center from 2010 to 2015, categorized by desensitization intensity: none/compatible (n = 260), low (0‐4 plasmaphereses, n = 47), moderate (5‐9, n = 74), and high (≥10, n = 94). The 1‐year cumulative incidence of infection was 50.1%, 49.8%, 66.0%, and 73.5% for recipients who received none, low, moderate, and high‐intensity desensitization ( P  < .001). The most common infections were UTI (33.5% of ILDKT vs. 21.5% compatible), opportunistic (21.9% vs. 10.8%), and bloodstream (19.1% vs. 5.4%) ( P  < .001). In weighted models, a trend toward increased risk was seen in low (wIRR = 0.77 1.402.56, P  = .3) and moderately (wIRR = 0.88 1.352.06, P  = .2) desensitized recipients, with a statistically significant 2.22‐fold (wIRR = 1.33 2.223.72, P  = .002) increased risk in highly desensitized recipients. Recipients with ≥4 infections were at higher risk of prolonged hospitalization (wIRR = 2.62 3.574.88, P  < .001) and death‐censored graft loss (wHR = 1.15 4.0113.95, P  = .03). Post–KT infections are more common in desensitized ILDKT recipients. A subset of highly desensitized patients is at ultra‐high risk for infections. Strategies should be designed to protect patients from the morbidity of recurrent infections, and to extend the survival benefit of ILDKT across the spectrum of recipients. Abstract : Among living donor kidney transplant recipients, infections are most common in patients who receive high‐intensity desensitization, and patients with more than 4 infections in the first year posttransplant are at increased risk of adverse outcomes.